2009
DOI: 10.1508/cytologia.74.201
|View full text |Cite
|
Sign up to set email alerts
|

Mutagenic Effect of Three Nitrogenous Fertilizers on Drosophila melanogaster

Abstract: SummaryThe present study was carried out in order to evaluate the mutagenic effect of 3 nitrogenous fertilizers; urea, ammonium nitrate and calcium nitrate; on Drosophila melanogaster. Newly hatched larvae were treated with the LC 25 and LC 50 of the 3 tested nitrogenous fertilizers. The classic sex-linked recessive lethal (SLRL) test was used to detect the differential mutagenic effect of the fertilizers on the 3 germ stages. The results showed that all fertilizers exhibited variable mutation frequencies in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
2
1
0
Order By: Relevance
“…Urea exhibited a direct mutagenic effect on postmeiotic stages, whereas ammonium nitrate and calcium nitrate revealed an indirect mutagenic effect on meiotic and pre-meiotic stages in Drosophila melanogaster, as reported by El-Din et al (2009). This study showed that the tested nitrogenous fertilizers possesses mutagenic potentialities which are related to their nitrogen content, as also reported by Arora et al (2014) with AT.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Tisupporting
confidence: 78%
“…Urea exhibited a direct mutagenic effect on postmeiotic stages, whereas ammonium nitrate and calcium nitrate revealed an indirect mutagenic effect on meiotic and pre-meiotic stages in Drosophila melanogaster, as reported by El-Din et al (2009). This study showed that the tested nitrogenous fertilizers possesses mutagenic potentialities which are related to their nitrogen content, as also reported by Arora et al (2014) with AT.…”
Section: Cyto-genotoxicity Of Fertilizers Monitored By Allium Root Tisupporting
confidence: 78%
“…Similar cytotoxic effects of other fertilizers has been shown by Chaudhari and Chaudhari (2013) and Oney and Tabur (2013). There are reports of mutagenic effects of N fertilizers in animals also (El-Din et al 2009).…”
Section: Introductionsupporting
confidence: 81%
“…in Vicia hybrida (Tabur and Oney 2009). El-Din et al (2009) observed mutagenic potentialities of N fertilizers in animals also. Some reports showed the cytogenotoxic effects of fertilizers on Vicia faba and Allium cepa (Oney and Tabur 2013, Verma et al 2016, Verma and Srivastava 2017.…”
mentioning
confidence: 89%